Evaluasi Implementasi Manajemen Rumah Sakit dalam Upaya Peningkatan Rating Google Customer Review di Rumah Sakit Karisma Cimareme Tahun 2023: Pendekatan Teori SERVQUAL dan Donabedian - Trenggono, Patriot Haryo; Bachtiar, Adang (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2025)
This study aims to evaluate the management of Karisma Cimareme Hospital in addressing its low Google Customer Review ratings. Initial data shows that KCH received an average rating of 2.9 stars, lower than two other private hospitals in West Bandung Regency, IMC Hospital with 3.1 stars and Cahya Kawaluyan Hospital with 4.1 stars. Using the SERVQUAL framework, which includes the dimensions of tangibles, empathy, responsiveness, reliability, and assurance, along with Donabedian's theory, this study focuses on improving service quality through the implementation of Standard Operating Procedures (SOP). The research method involved direct observation of hospital services, in-depth interviews with hospital staff, and analysis of Google Customer Reviews. Data were analyzed using a thematic approach to identify key factors influencing patient reviews and ratings. The results showed that every dimension in the SERVQUAL model significantly affected customer evaluations. The implementation of SOP, involving various parties such as service managers, heads of medical support, head nurses, public relations and marketing teams, and the PIPP team, successfully increased the Google Customer Review rating by 0.7 points, from 2.9 to 3.6. This improvement highlights the importance of a structured approach to enhancing service quality and customer perception. This study provides insights into the challenges faced by hospitals in managing online reviews and offers strategic guidelines for improving patient satisfaction, hospital reputation, and online review management.